The impact of fiscal decentralization and intergovernmental competition on the local government debt risk: Evidence from China - Huo, Xuling; Bi, Shulei; Yin, Yushi (Frontiers in Environmental Science, 2023)
Preventing and defusing the risk of local government debt is of great significance for stabilizing the sustained and healthy development of China’s local economy. Based on the data of explicit debt and implicit debt of local governments in China from 2012 to 2020, this paper theoretically analyzes and empirically tests the spatial correlation effect of fiscal decentralization and intergovernmental competition on local government debt risk. It’s found that local government debt risk has obvious inertia effect in time and positive spatial correlation effect in space, and local fiscal spending decentralization and intergovernmental competition have a significant positive impact on the local government debt risk, as well as a positive spatial spillover effect. The research of this paper has very important policy implications for perfecting China's decentralization system, standardizing the competition among governments, and preventing and defusing local government debt risks.